Membangun Kemandirian Perempuan Melalui Keterampilan Kewirausahaan untuk Meningkatkan Kesejahteraan Keluarga: (Implementasi Project Based Learning di Desa Legok Kidul Kecamatan Paseh Kabupaten Sumedang) - Saepudin, Asep; Susanto, Eri; Ningrum, Dedah; Retno Anggraini, Diah; Rindiani, Ani (LPPM Universitas Koperasi Indonesia, 2024)
Poverty is a social problem that is defined as a situation where a person is unable to maintain himself according to the standard of living of the group and is also unable to utilize his mental and physical energy within the group. This poverty does not just happen. Many factors cause poverty, including (a) individual factors, (b) social factors, and (c) cultural factors. The impact of poverty is clearly felt by many parties, including married women, their situation is very diverse, there are women who are divorced by their husbands, or even left by their husbands, or they have husbands but their husbands do not support them and their families, so they choose to struggle alone to support themselves and their families. This problem must be addressed immediately, how to prepare PRSE to be able to meet the needs of their families, through various empowerment efforts in order to prepare them to become independent women who carry out multiple roles. Based on this phenomenon, educational solutions are needed, including training programs in the form of project Based Learning (PBL) to build women's independence through entrepreneurial skills to improve family welfare in Legok Kidul Village, Paseh District, and Sumedang Regency. The training program was implemented through the stages of identification of needs, coordination of activities, development of program design, program action, and reporting and publication.